A qualitative exploration of the experience of individual-level stigma among adolescents with a chronic illness - Joan A. Thomas; Garth Lipps (PLoS ONE, 2025)
Background Much of the research measuring stigma experience related to illness in children and adolescents has been conducted using measures developed from adult perspectives. However, children and adolescents are different from adults developmentally, and stigma is a subjective concept. As the first step in a multi-phase process to develop generic measures of individual-level stigma for use with adolescents with an illness, a qualitative study was conducted to explore the lived experiences of the different forms of individual-level stigma among adolescents with various illnesses. Methods Semi-structured interviews, utilizing multiperspectival interpretive phenomenological analysis, were conducted to identify commonalities in the experiences of perceived, enacted, and internalized stigma among adolescents with different chronic conditions recruited from illness-specific clinics at 2 general hospitals and a public clinic. Results The adolescents’ experience of perceived stigma was centered on negative treatments they anticipated receiving due to their illnesses, rather than a focus that also included awareness of illness-specific stereotypes, as suggested by the Modified Labelling Theory. Their awareness of illness-specific stereotypes was limited and mainly internalized, manifesting itself as negative self-beliefs. Their fear of negative treatments, also internalized, led them to conceal their illnesses and have negative feelings about themselves. They experienced enacted stigma mainly in interpersonal relationships in overt and subtle ways. Their interpretations of some of the treatments they received from others influenced their experience of enacted stigma. Furthermore, the adolescents’ experience of individual-level stigma was influenced by their level of development, cognitive maturity, and changes in their peer groups. Also, their experience of stigma bore some similarities with adults. Conclusions The study found that the adolescents’ experience of the different forms of individual-level stigma bore some similarities with adults as well as there were differences. The differences were due to the influence of social and cognitive development. The findings should inform quantitative assessments of individual-level stigma in adolescents with an illness.